A secure authentication method based on hash function for RFID system - Chuan LI; Xuejun LI (Dianxin kexue)
Limited by the tag chip resource of a radio-frequency identification (RFID) system,the data and information security has been an important issue of an RFID system.The one-way Hash function provides an efficient and reliable approach for the identification and authentication of the RFID system.Based on the analysis of several typical Hash authentication protocols,a novel secure authentication protocol based on the Hash function was proposed.The protocol was intended to tackle the identification among the handheld RFID reader,tags and server.Specifically,the protocol utilizes the Hash function to achieve the mutual authentication between the above three objects.The performance analysis shows that the proposed protocol can resist the most known attacks with reduced storage capacity and lower computation overhead.Therefore,the proposed strategy effectively ensures the data and privacy security of the RFID system,achieving the bidirectional anonymous authentication between the terminal and server,which is very suitable for the distributed large-scale RFID system.